POTENSI KESENIAN JATHILAN UNTUK PENCIPTAAN FILM - Maharani Nur Azizah; Ranang Agung Sugihartono; Farhana Aulia (ROLLING, 2023)
Jathilan art as a traditional Javanese dance is still alive today in the countryside. One of them is the Jathilan Tunggal Budhi art community in Gobeh village, Ngadirojo District, Wonogiri Regency which is driven by local youths. The purpose of this study is to reveal the potential of jathilan art as a source of film creation ideas. Research with a focus on the potential contained in this art is a type of qualitative research. Data collection uses the observation method and literature study and is processed by qualitative data analysis. The result of the study shows that jathilan art has the potential to be used as a source of inspiration for film creation, both fiction and documentary. Story, movement, musical rhythm, and properties can be developed in the film creation process. The movement in the jathilan dance and such the wild horse's irregular movement can give a strong impression of mystery and horror, so that it can become interesting adventures through interpretable story plots. The nuances of gamelan accompaniment music can also give strength to the cinematic elements and artistic arrangements of the film. Traditional art that is synonymous with old-fashioned, but in fact young people are involved in it and adaptive to technology and social media can be a special attraction. Film produced is not only for entertainment but can also be a form of Indonesian cultural diplomacy when film is distributed abroad.